Unsafe Drinking Water Is Associated with Environmental Enteric Dysfunction and Poor Growth Outcomes in Young Children in Rural Southwestern Uganda - Lauer, Jacqueline M.; Duggan, Christopher P.; Ausman, Lynne M.; Griffiths, Jeffrey K.; Webb, Patrick; Bashaasha, Bernard; Agaba, Edgar; Turyashemererwa, Florence M.; Ghosh, Shibani (The American journal of tropical medicine and hygiene, 2018)
Environmental enteric dysfunction (EED), a subclinical disorder of the small intestine, and poor growth are associated with living in poor water, sanitation, and hygiene (WASH) conditions, but specific risk factors remain unclear. Nested within a birth cohort study, this study investigates relationships among water quality, EED, and growth in 385 children living in southwestern Uganda. Water quality wasassessed using a portable water quality testwhen children were 6 months, and safe water was defined as lacking Escherichia coli contamination. Environmental enteric dysfunction was assessed using the lactulose:mannitol (L:M) test at 12–16 months. Anthropometry and covariate data were extracted from the cohort study, and associations were assessed using linear and logistic regression models. Less than half of the households (43.8%) had safe water, and safe versus unsafe water did not correlate with improved versus unimproved water source. In adjusted linear regression models, children from households with safe water had significantly lower logtransformed (ln) L:M ratios (β: −0.22, 95% confidence interval (CI): −0.44, −0.00) and significantly higher length-for-age (β: 0.29, 95% CI: 0.00, 0.58) and weight-for-age (β: 0.20, 95% CI: 0.05, 0.34) Z-scores at 12–16 months. Furthermore, in adjusted linear regression models, ln L:M ratios at 12–16 months significantly decreased with increasing length-for-age Z-scores at birth, 6 months, and 9 months (β: −0.05,95%CI: −0.10, −0.004; β: −0.06,95%CI: −0.11, −0.006; and β: −0.05, 95%CI: −0.09, −0.005, respectively). Overall, our data suggest that programs seeking to improve nutrition should address poor WASH conditions simultaneously, particularly related to household drinking water quality.
Keywords: Drinking Water; Environmental Enteric Dysfunction; Poor Growth Outcomes; Young Children; Rural Southwestern Uganda